UPAYA PENERAPAN MODEL COOPERATIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN PENJASORKES KOMPETENSI DASAR BELADIRI KARATE KELAS XI-RPL.1 SMKN 2 PRAYA TENGAH - Ely Kusumastuti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
The purpose of this study was to determine student learning outcomes with the application of cooperative learning models in improving student learning outcomes Penjasorkes subject of Self Defense Basic Competence with martial arts subject matter Karate class XI-RPL.1 Middle Praya 2 Vocational High School 2015/2016 academic year. The subjects in this study were students of class XI-RPL.1 in the 2015/2016 school year which amounted to 30 students consisting of 12 male students and 18 female students. The research method uses a classroom action research method consisting of 2 cycles of action. Each cycle consists of four stages including planning, implementation, observing the results of actions, and reflection. Based on the results of the evaluation of learning prior to the application of cooperative learning in Karate Martial Arts with students completing 26 students (86.66%), and 4 students (13.33%) stated to be incomplete, then action in the first cycle required 19 students (63.33%), and 11 students (36.67%) stated that they were not completed with KKM 76, the highest score was 90 and the lowest score was 69 while the average score was 70.00 so there was a need for improvement in the next cycle, with classical completeness of 63.33 Levels of mastery of subject matter 1 person (3.33%) high ability category, 18 people (60.00%) moderate ability category, and 11 students (36.67%) low category. The results of the implementation of the second cycle evaluation were stated by 27 students or (90%) declared complete, and 3 students or (10.00%) were declared incomplete with KKM 76 The highest score was 94 and the lowest score was 67 Students who reached the ability standard category category height of 10 students or 33.33%. Students who get the ability of the medium category are 17 students or 56.67% and students who have low abilities are 3 people or 10.00%. While the percentage of classical completeness obtained was 93.33%, there was an increase in classical completeness from cycle I and cycle II at 30.00%. The conclusions of the study are that the application of cooperative learning can improve optimal learning outcomes in the XI-RPL class.1 odd semester at Central Praya 2 Vocational School in Central Lombok Regency Academic Year 2015/2016.